Required effort for shaft/ring setting according to roughness due to CNC lathe machining - Salgado Cruz, Manuel; Estrada Barbosa, Quirino; Cortes Garcia, Claudia; Szwedowicz, Dariusz; Martinez Rayon, Eladio; Blanco Ortega, Andres (2020)
The shaft/hub joints use the difference in diameters to make the assembly, either by pressure or by temperature. In this investigation, a study was made of the effect of roughness in an assembly, represented by the inner ring of a bearing whose internal diameter is taken as a fixed reference, with different shafts. The shafts were machined on a CNC lathe at different feed rates for each. These variations modified the size of the surface roughness and were performed to determine the effect of roughness on tolerances. Compression assembly-disassembly tests were performed with the bearing and arrows at the shaft/ring joints to determine maximum force. A model was developed by the MEF finite element method of the shaft/ring draft. The surfaces in contact were plotted smooth, to determine the interference value that represents the roughness obtained from turning. To validate the model, contact pressure and extraction force results were compared with the thick wall cylinder theory. The results obtained demonstrate that a greater surface roughness obtained by varying the feed rate during the machining of the arrow on the lathe, contributes to the increase in the load capacity of this type of joint. Finally, based on the tests carried out, a modification was proposed in the adjustment contact pressure equation to consider this trend.